Pressure and Temperature Dependence of Local Structure and Dynamics in an Ionic Liquid - Lundin, Filippa (J Phys Chem B, 2021)
[Image: see text] A detailed understanding of the local dynamics in ionic liquids remains an important aspect in the design of new ionic liquids as advanced functional fluids. Here, we use small-angle X-ray scattering and quasi-elastic neutron spectroscopy to investigate the local structure and dynamics in a model ionic liquid as a function of temperature and pressure, with a particular focus on state points (P,T) where the macroscopic dynamics, i.e., conductivity, is the same. Our results suggest that the initial step of ion transport is a confined diffusion process, on the nanosecond timescale, where the motion is restricted by a cage of nearest neighbors. This process is invariant considering timescale, geometry, and the participation ratio, at state points of constant conductivity, i.e., state points of isoconductivity. The connection to the nearest-neighbor structure is underlined by the invariance of the peak in the structure factor corresponding to nearest-neighbor correlations. At shorter timescales, picoseconds, two localized relaxation processes of the cation can be observed, which are not directly linked to ion transport. However, these processes also show invariance at isoconductivity. This points to that the overall energy landscape in ionic liquids responds in the same way to density changes and is mainly governed by the nearest-neighbor interactions.